Effects of the Gas/Solids Distribution on the Local and Overall Solids Distribution in a Downer Reactor - Wirth, Karl-Ernst; Lehner, Peter (Canadian Journal of Chemical Engineering, 1999)
In the last few years, the downer has been proposed as a new reactor for gas/solids reactions. Compared to state-of-the-art riser reactors, the cocurrent downflow of gas and solids should lead to a more uniform flow structure, close to plug flow. Experimental studies showed, that the gas/solids distributor at the top of the reactor is significantly influencing the flow pattern in a downer reactor. Local information about the solids concentration is indispensable for a thorough characterization of the flow structure in gas/solids flows. To obtain this information, x-ray computed tomography has been used for the experimental investigations.
UnivIS-Import:2015-03-05:Pub.1999.tech.ITC.mechve.effect
Keywords: Circulating fluidized bed; Downer reactor; Gas/solids flow; Tomography